An Overview of an Arbitral Award in Libya: An Analytical Study - Omar Nayed, Murad Idris (South Asian Journal of Social Sciences and Humanities, 2023)
Arbitration has become the most popular dispute resolution mechanism all over the world  because of the finality of the arbitral award. In the context of this article, the legal approaches  distinguishing between domestic and foreign arbitral award are very important and these legal  approaches differ from one arbitration law to another. By using doctrinal legal research  methodology, this paper aims to comprehensively analyse the arbitral award in Libya. Data  collected through library-based approach and both types of data are analytically examined. This  article found that the Libyan law of Civil and Commercial Procedures of 1953 has several legal  gaps that need to be addressed in order to bring it in line with modern arbitration laws globally.  The article then goes on to make several recommendations for improving the Libyan law.
Keywords: arbitration; arbitral award; Dispute resolution; Libya